DEVELOPMENT OF LANTERN DESIGN FOR THE CLIMATE CONTROL SYSTEM OF THE BUILDING (Collection of scientific works «Modern structures of metal and wood», 2024)
Modern residential buildings are increasingly equipped with specialized climate control systems. Such systems are constantly becoming more complicated and nowadays allow to control  and,  if  necessary,  maintain  at  a  given  level  a  whole  series  of  parameters  in  structures  - temperature  and  humidity  of  air,  its  degree  of  purity  and  ionization,  temperature  and  quality  of water, level of illumination and irradiation,  as well as technical design parameters. Placement of such climate control systems for low-rise residential buildings is assumed in the building itself, but for  high-rise  buildings  such  systems  are  placed  on  the  roof.  In  this  case,  the  practical  task  of protecting climate control systems from the dangerous action of aggressive external factors arises. The  paper  proposes  the  development  of  a  special  protective  lantern  capable  of  performing such  a  function.  Structurally,  the  lantern  consists  of  a  steel  frame  made  of  bent-welded  square profiles and translucent filling. Four architectural and constructive versions of the protective lantern are considered - arched, pyramidal-elongated, pyramidal and spherical. To select the most rational constructive option, numerical modeling was performed based on the finite element method using the domestic software product SCAD. Its results made it possible to choose the necessary cross-sections of the frame  elements in accordance  with the construction current standards in Ukraine. Based on the comparison of mass indicators and the market value of protective lantern materials, it was finally determined that the spherical lantern has the lowest indicators and is the most rational. However, for real buildings that have rectilinear load-bearing structural elements, this option may not be effective and may require reworking of the load-bearing structures. Therefore, for practical implementation  an  arched  design  version  of  the  protective  lantern  was  chosen.  This  option  is recommended  for  practical  implementation  in  the  reconstruction  project  of  a  multi-story commercial-office-hotel complex in the city of Pavlograd.